2021
DOI: 10.1007/s40200-021-00768-5
|View full text |Cite
|
Sign up to set email alerts
|

Proportion and mortality of Iranian diabetes mellitus, chronic kidney disease, hypertension and cardiovascular disease patients with COVID-19: a meta-analysis

Abstract: Background Currently, the number of patients with SARS-COV-2 infection has increased rapidly in Iran, but the risk and mortality of SARS-COV-2 infection in Iranian patients with diabetes mellitus (DM), chronic kidney disease (CKD), hypertension and cardiovascular diseases (CVDs) still not clear. The aim of this meta-analysis was to estimate the proportion and mortality of SARS-COV-2 in these patients. Methods A comprehensive literature search was carried out in PubMed, Web of Sciences, Cochrane Library, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 65 publications
6
29
1
Order By: Relevance
“…Among patients with COVID-19 hospitalized in 30 Polish centers included in the current analysis, nearly 20% were diagnosed with CKD, of which 18% presented severe renal failure. In addition to the worse patient’s status regarding the severity of COVID-19 when admitted to the hospital, we found the pre-existing renal disease to be independently associated with higher in-hospital mortality, especially in those with severe kidney failure, and our findings are in line with the results of previous studies [ 13 , 14 , 22 , 23 , 24 , 25 , 26 ]. The Global Burden of Disease (GBD) collaboration recently estimated the risk factors for severe COVID-19 worldwide using results from international databases and large multimorbidity studies from different countries, and determined that CKD is a condition conveying the highest risk for the severe presentation of the disease and COVID-19-related death [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among patients with COVID-19 hospitalized in 30 Polish centers included in the current analysis, nearly 20% were diagnosed with CKD, of which 18% presented severe renal failure. In addition to the worse patient’s status regarding the severity of COVID-19 when admitted to the hospital, we found the pre-existing renal disease to be independently associated with higher in-hospital mortality, especially in those with severe kidney failure, and our findings are in line with the results of previous studies [ 13 , 14 , 22 , 23 , 24 , 25 , 26 ]. The Global Burden of Disease (GBD) collaboration recently estimated the risk factors for severe COVID-19 worldwide using results from international databases and large multimorbidity studies from different countries, and determined that CKD is a condition conveying the highest risk for the severe presentation of the disease and COVID-19-related death [ 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…The impact of coexisting diseases was investigated in many studies and results are divergent depending on the analyzed population, sample size, and the nature of the study. Meta-analysis performed among Iranian patients by Merjalili et al revealed that diabetes was associated with higher mortality, while arterial hypertension was not [ 26 ]. Park et al analyzed the Korean population and found both diabetes and hypertension to be risk factors for death in the course of COVID-19 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persistent renin-angiotensin-aldosterone system (RAAS) activation and disruption in central metabolism encourage proteinuria and renal fibrosis [ 38 , 39 , 40 ]. There are recent reports of SARS-CoV-2 infections in diabetes and DKD [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Figure 1 demonstrates the role of RAAS in the understanding of SARS-CoV-2 in diabetes.…”
Section: Diabetic Kidney Diseasementioning
confidence: 99%
“…The patient was admitted under the impression of diabetic ketoacidosis (DKA). The initial laboratory data (with normal range in parenthesis) showed a high Blood Sugar level (BS): 487 mg/dL (< 140), HbA1c: 7.2% (< 6.5%), pH: 6.7 (7.35-7.45), Bicarbonate (HCO 3 ): 4.2 mEq/L (22-26), Anti GAD65: negative, Insulin Antibody (Ab): negative, Carbon Dioxide (pCO 2 ): 21.7 mmHg (30-50), Urine Ketone: 1 + , Sodium (Na): 128 mEq/L (134-145), Potassium (K): 2.5 mEq/L (3.5-5.5), WBC: 11,400 /µL (3500-10,000), RBC: 6,100,000 /µL (3,600,000-6,100,000), Hemoglobin: 15 gr/dL (11.5-18.8), PLT: 354 /mL (150-450), CRP: negative, Magnesium (Mg): 2.2 mg/dL (1.5-2.3), Phosphorus (P): 1.7 mg/dL (3.9-7.7), Blood Urea Nitrogen (BUN): 90 mg/dL (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and Creatinine (Cr): 0.6 mg/dL (0.7-1.4). Additionally, due to the patient's contact with his mother, all the laboratory workups related to COVID-19 were done.…”
Section: Case Reportmentioning
confidence: 99%
“…Recently, evidence showed that an association may exist between diabetes and higher risk of COVID-19 infection and the increased mortality rate [6]. On the other hand, in some people infected with COVID-19, new-onset diabetes has been reported and in some others, severe metabolic complications occurring in PWD have been observed [7][8][9].…”
Section: Introductionmentioning
confidence: 99%